Radioactive waste technical and normative aspects of its disposal - Streffer, Christian (Ethics of Science and Technology Assessment, 2012)
Waste caused by the use of radioactive material in research, medicine and technologies, above all high level waste from nuclear power plants, must be disposed of safely. However, the strategies discussed for the disposal of radioactive waste as well as proposals for choosing a proper site for final waste disposal are strongly debated. An appropriate disposal must satisfy complex technical requirements and must meet stringent conditions to appropriately protect man and nature from risks of radioactivity over very long periods. Ethical, legal and social conditions must be considered as well. An interdisciplinary team of experts from relevant fields compiled the current status and developed criteria as well as strategies which meet the requirements of safety and security for present and future generations. The study also provides specific recommendations that will improve and optimize the chances for the selection of a repository site implementing the participation of stakeholders including the general public and not neglecting the responsibility of the legal institutions. The study provides an advanced and, due to its interdisciplinary approach, novel contribution to the corresponding scientific debates including normative and social aspects of acceptability and acceptance. At the same time it serves as a contribution to public and political debates presenting an easily comprehensible executive summary and describing practicable recommendations.